The narrative of the woman caught in adultery (JN 7:53-8:1-11) re-read in the Nigerian context - C. U. Manus; J. C. Ukaga (Acta Theologica)
This article draws on the spirit and letters of the Vienna Declaration and its Program of Action that emanated from the World Conference on Human Rights held in 1993. It delineates the fact that Women’s rights are essential aspects of the fundamental human rights of every individual. With the synchronic study of the receivers as our methodology, we expose the narrative of the unnamed adulteress woman in John 7:53-8:1-11, in order to seek a theological grounding for women’s human rights in the context of Nigeria, where Boko Haram’s dehumanization of the Chibok girls and other women is rife, and explore the Nigerian history of women activists. We exegetically expose the storyline of the text of John and contrast the ideas with the horrific incidence of women’s degradation in Nigeria. The findings reveal abiding lessons adjudged relevant for a sustainable pro-life Christology and theology of the rescue and liberation of women from militant jihadists in north-eastern Nigeria. For Jesus, women are divinely blessed with equal rights with men.